Successful Treatment of MMP-9-Expressing Angiosarcoma with Low-Dose Docetaxel and Bisphosphonate - Masaya Ishibashi; Taku Fujimura; Akira Hashimoto; Takahiro Haga; Kaoru Onami; Akira Tsukada; Yumi Kambayashi; Takanori Hidaka; Sadanori Furudate; Ryoko Shimada; Setsuya Aiba (Karger Publishers, 2012)
We describe a 78-year-old Japanese patient with angiosarcoma on the scalp. Interestingly, immunohistochemical staining revealed this tumor as positive for matrix metalloproteinase 9 (MMP-9). After conventional therapy for angiosarcoma with surgical treatment and radiation therapy, we intravenously administered docetaxel at 40 mg/m2 body surface area together with oral administration of 17.5 mg sodium risedronate hydrate. One and a half years after the standard treatment, there was no evidence of local recurrence or metastasis.